Development of novel force-limiting grasping forceps with a simple mechanism. (6th June 2018) - Sakaguchi, Yasuto; Sato, Toshihiko; Yutaka, Yojiro; Muranishi, Yusuke; Komatsu, Teruya; Yoshizawa, Akihiko; Nakajima, Naoki; Nakamura, Tatsuo; Date, Hiroshi
Abstract: OBJECTIVES: In endoscopic surgery, fragile tissues may be damaged by the application of excessive force. Thus, we developed novel endoscopic forceps with a simple force-limiting mechanism. METHODS: The novel forceps were constructed with a leaf spring, and the spring thickness determines grasping pressure. We established an evaluation system (maximum score is 11 points) for lung tissue damage leading to complications. We tested the conventional forceps (186.8 kPa) and 3 novel spring forceps with the following thicknesses: 1.3 mm (53.0 kPa), 2.2 mm (187.7 kPa) and 2.8 mm (369.2 kPa). After grasping, peripheral canine lung tissues were microscopically examined for acute- and late-phase damages. RESULTS: In the acute phase (20 sites), the novel forceps caused capillary congestion and haemorrhage in the subpleural tissue, whereas the conventional forceps caused deep tissue and pleural damages. In the late phase (30 sites), both forceps caused fibroblast formation and interstitial thickening, which progressed to the deeper tissues as grasping pressure increased. In the acute phase, the median scores were 2.0 and 6.0 for the novel and conventional forceps, respectively ( P  = 0.003). In the late phase, the median scores were 2.0, 2.5 and 5.0 for 1.3-, 2.2- and 2.8-mm thick forceps, respectively, and 5.0 for the conventional forceps ( P  < 0.001). In both phases, the novel forceps with grasping pressure set below 187.7 kPa (2.2 mm) caused significantly less lung tissue damage than the conventional forceps. CONCLUSIONS: The novel endoscopic forceps are able to regulate the tissue-grasping pressure and induce less damage in lung tissues than conventional forceps.